Pengaruh Model Pembelajaran Teams Game Tournament Terhadap Motivasi Belajar Pada Pembelajaran Akidah Akhlak Kelas VIII MTs Swasta Gantung Ciri - Lisa Eka Putri; Deswalantri Deswalantri; Al-Baihaqi Anas; Eka Rizal (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
The The background of this research is that the learning process is still centered on the teacher (teacher center) which makes the teaching and learning process passive and also the teacher only uses conventional models. This will have an impact on student learning motivation to be low. Given the importance of setting strategies and variations in classroom learning will have implications for student learning motivation, therefore researchers are interested in using the Teams Games Tournament type cooperative learning model to measure how much influence the Teams Games Tournament learning model has on student learning motivation. This study aims to determine the magnitude of the influence of the Teams Games Tournament (TGT) model on student learning motivation in learning the moral creed of class VIII MTs Gantung Ciri. The type of research used is a quasi experiment with a posttest-only research design with non-equivalent groups. The sampling technique uses non-probability sampling or is called saturated sampling. Saturated sampling is a sampling technique when all members of the population are used as samples. Class VIII-1 as an experimental class with 22 students. Class VIII-2 as the control class with 21 students. The data analysis technique was carried out by carrying out a normality test with the Shapiro-Wilk formula, homogeneity test and then testing the hypothesis with an independent t-test. All tests were performed using the SPSS 22 application. The results of the study obtained from the research data that the average results of the experimental class learning motivation questionnaire = 63.09 and the control class = 59.71. It can be concluded that the average results of the experimental class questionnaire are higher than the average results of the control class questionnaire and the results of the hypothesis which was carried out with the t-test obtained the number 0.043 <0.05 then Ho was rejected and Ha was accepted.